2007
DOI: 10.1159/000104265
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Photopheresis as a Treatment for Patients with Severe, Refractory Atopic Dermatitis

Abstract: Introduction: Atopic dermatitis (AD) is a complex disease with a variety of possible treatment regimens. The study objective was to demonstrate that methoxsalen used in conjunction with the Uvar XTS photopheresis system (Therakos, Exton, Pa., USA) is safe and can have a clinical effect on the skin manifestations and the quality of life in patients with severe, refractory AD. Methods: Single-arm, open-label treatment using the Uvar XTS photopheresis system. Seven patients (4 male and 3 female, median age: 47 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 25 publications
2
28
0
3
Order By: Relevance
“…Similar findings regarding ECP treatment have been published in epidermolysis bullosa [51], chronic erosive lichen planus [52] and atopic dermatitis [53]. Unfortunately, the authors only reported on single-center, small non-randomized patients series.…”
Section: Ctclsupporting
confidence: 61%
“…Similar findings regarding ECP treatment have been published in epidermolysis bullosa [51], chronic erosive lichen planus [52] and atopic dermatitis [53]. Unfortunately, the authors only reported on single-center, small non-randomized patients series.…”
Section: Ctclsupporting
confidence: 61%
“…72 Furthermore, improvement in the Scoring of Atopic Dermatitis score with ECP has been found to be associated with improvements in some measures of patient quality of life. 73 Larger, comparative studies are now required to evaluate further the therapeutic potential of ECP in this indication.…”
Section: Ecp In Other Diseasesmentioning
confidence: 99%
“…Atopic dermatitis is an immune-mediated, relapsing skin disorder for which treatment options include a variety of emollients, corticosteroids, immunomodulators, and phototherapy [143]. Atopic dermatitis patients who failed to respond to standard first-and/or second-line therapies showed substantial skin responses to ECP treatment within 6-10 cycles, indicating that photopheresis may have beneficial therapeutic effect in patients who are refractory to conventional therapy [144]. In addition, lichen planus is a chronic mucocutaneous disease that can develop on the skin, mouth, scalp, genitals, or nails.…”
Section: Studies In Natural Products Chemistrymentioning
confidence: 99%